KEWENANGAN PEMERINTAH DAERAH KABUPATEN KUDUS DALAM PENARIKAN RETRIBUSI TERMINAL TIPE C SEBAGAI PELAKSANAAN OTONOMI DAERAH - Maylani, Fita Fiana; Firdaus, Sunny Ummul (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
Regional autonomy demands local independence in governing its government one of them is the authority to form a Regional Regulation in managing the finances that can be seen from the size of the role of local revenue. This study analyzes and assesses the authority of the local government of Kudus District in the retribution of terminal type c as the implementation of regional autonomy. This research is a descriptive-qualitative legal research. Data collection techniques were conducted through field interviews. The results of this study indicate that the authority of the local government of Kudus District in the withdrawal of terminal type c retribution as the implementation of regional autonomy is implemented by the mechanism of levy withdrawal through stage (1) planning, (2) organizing, (3) , and (3) controlling. The mechanism has been adjusted to the provisions of Local Regulation of Kudus number 6 Year 2011 on Terminal Retribution. The mechanism of withdrawal of type c terminal retribution in Kudus district becomes an authority of the local government of Kudus Regency as the implementation of regional autonomy.